Budget Impact Analysis Of Subcutaneous Belimumab In Patients With Systemic Lupus Erythematosus In Spain - Cevey M; Calvo-Alén J; Crespo C; Robles-Marhuenda A; Smolen L; Cortés-Hernández J (Dove Medical Press, 2019)
Maria Cevey,1 Jaime Calvo-Alén,2 Carlos Crespo,3 Angel Robles-Marhuenda,4 Lee Smolen,5 Josefina Cortés-Hernández6 1Department of Market Access, GlaxoSmithKline SA, Madrid, Spain; 2Department of Rheumatology, University Hospital Araba, Vitoria, Spain; 3Department of Genetics, Microbiology and Statistics, Statistics Section, University of Barcelona, Barcelona, Spain; 4Department of Internal Medicine, Hospital La Paz, Madrid, Spain; 5Modeling & Analytics, Medical Decision Modeling Inc, Indianapolis, IN, USA; 6Department of Internal Medicine, Vall d’Hebron Institut de Recerca (VHIR), Barcelona, SpainCorrespondence: Josefina Cortés-HernándezDepartment of Internal Medicine, Vall d’Hebron Institut de Recerca (VHIR), Vall d’Hebron University Hospital Research Institute, Passeig Vall d’Hebron 119-129, Barcelona 08035, SpainTel +34 934893000Fax +34 934894438Email fina.cortes@vhir.orgObjective: To evaluate the budget impact and the direct costs of the introduction of subcutaneous belimumab (SC) into the Spanish National Health Service (NHS) for patients with systemic lupus erythematosus (SLE) in Spain.Methods: This study was conducted from the Spanish NHS perspective with a time horizon of 3 years. The budget impact analysis compared the cost difference between two scenarios: current market (standard therapy (ST) and intravenous belimumab (IV)) and other market in which patients switched from belimumab IV to belimumab SC until reaching 17% of the total market share. The eligible population was calculated to receive treatment with belimumab, applying the EPISER (study of the prevalence of rheumatic diseases in adult population in Spain) prevalence (91 per 100,000 inhabitants), Autoimmune Systemic Diseases Study Group (GEAS) incidence (2 per 100,000 inhabitants), and the risk of annual mortality to the Spanish adult population. Patients with severe active lupus nephritis and with severe active CNS lupus were excluded. Patients’ characteristics, flare rates and severity, and healthcare resource consumption were evaluated based on data from the literature and interviews with an expert panel. A sensitivity analysis was performed.Results: Currently, there is an estimated 34,697 adult patients with SLE in Spain and 3849 patients who are eligible to be treated with belimumab. The introduction of belimumab SC into the Spanish NHS could generate savings in direct healthcare costs of 6 million euros over the 3 years.Conclusion: The introduction of belimumab SC shows direct savings for the Spanish NHS. These savings could contribute to sustainability and decision-making.Keywords: belimumab, budget impact, Spanish National Health Service, NHS, Systemic Lupus Erythematosus